1994
DOI: 10.1002/sia.740210602
|View full text |Cite
|
Sign up to set email alerts
|

Towards the ultimate limits of depth resolution in sputter profiling: Beam‐induced chemical changes and the importance of sample quality

Abstract: Recent progress in materials characterization by sputter profiling is discussed, with particular emphasis on a critical evaluation of the parameters that determine the depth resolution. The net effect of beam‐induced material transport and sputtering can be studied in a straightforward manner using abrupt doping distributions embedded in the matrix of interest, parallel to its flat surface. It is shown that the quality of the data that can be obtained with modern instruments is sufficient to identify lack of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 74 publications
(13 reference statements)
2
19
0
Order By: Relevance
“…They do not actually coincide due to energy-and angledependent changes in the SIMS resolution function. 2,4 In agreement with many other works in the literature regarding SIMS depth proÐling of delta-doped distributions,2h8,19 the leading and trailing edges of the measured indium signal have an exponential behaviour characterized by a leading edge decay length j u (upslope) and a trailing edge decay length (downslope). j d The inset in Fig.…”
Section: High Depth Resolutionsupporting
confidence: 81%
See 1 more Smart Citation
“…They do not actually coincide due to energy-and angledependent changes in the SIMS resolution function. 2,4 In agreement with many other works in the literature regarding SIMS depth proÐling of delta-doped distributions,2h8,19 the leading and trailing edges of the measured indium signal have an exponential behaviour characterized by a leading edge decay length j u (upslope) and a trailing edge decay length (downslope). j d The inset in Fig.…”
Section: High Depth Resolutionsupporting
confidence: 81%
“…4 Nevertheless, several authors in latter years have shown that by using appropriate experimental conditions and particular technical and mathematical procedures, SIMS can reach high levels of performances in the analysis of very sharp elemental distributions.4h8…”
Section: Introductionmentioning
confidence: 99%
“…32 The results of Fig. 18 O 2à gree with the previous Ðndings in that the 0.5 keV proÐles measured at 0¡ and 75¡ exhibit essentially the same exponential tails. Hence, in terms of bombardmentinduced mixing, measurements with oxygen primary ions at rather oblique beam incidence (75¡) do not provide an advantage compared to 0¡.…”
Section: Some Aspects Of Bombardment-induced Boron Relocationsupporting
confidence: 77%
“…This lack of an improvement can be attributed, at least in part, to the favourable oxygen "bu †erÏ e †ect achieved at normal incidence. 32,56 In this context it is also worth mentioning that improvements in depth resolution, to be achieved by operating at oblique impact angles h, are often overestimated in the literature. It has been shown recently,57 for 0.6È2 keV bombardment at 44È80¡, that the h O 2 dependence of j(Ge in Si) has a form that may be written as with j(h) \ j 0 (sin2h s ] cos2h)0.5, sinh s \ 0.36.…”
Section: Some Aspects Of Bombardment-induced Boron Relocationmentioning
confidence: 98%
See 1 more Smart Citation